Liturgical furnishings in existing Modern style Roman Catholic Churches in Metro Manila - Bacosa, Frances Anna Valdez; Quevedo, Ma. Teresa (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ASBTRACT The study is a qualitative research that assessed the use of liturgical furnishings in existing modern style Roman Catholic churches and its implications in the practice of traditional church rituals. A multi-method approach using interview and visual documentation was employed in the study. Purposive sampling was utilized in the selection of six (6) Roman Catholic churches and eighteen (18) informants, six (6) of whom were parish priests and twelve (12) were parishioners. For data collection, an interview guide, visual documentation sheet, notebook, pen and voice recorder were used. The results showed that out of the thirteen (13) liturgical furnishings, only ten (10) were found to be present in all of the churches. These included the altar table, main lectern, commentator's lectern, presider's chair, tabernacle, baptismal font, pews with built-in kneelers, crucifix, Stations of the Cross and the choir seat. The presider's lectern. holy water font, and confessional box were not found in all of the churches. These liturgical furnishings greatly varied in their materials, placement, form, and style. However, despite the changes in the furnishings in terms of these design aspects, the use of liturgical furnishings in traditional rituals was still the same with the way they were used since the Vatican II. Some changes in their use only occurred during pastoral necessities or situations when the church needed immediate resolutions to such as in mass celebrations when practicality was more needed and prioritized. Furthermore, the change in the physical character of the furnishings did not directly affect the observance of the rituals; rather, the change in the rituals affected the physical character of the furnishings.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Catholic church buildings -- Philippines